The Impact of Personnel and Materiel Readiness of the Garuda Contingent in UNIFIL on Mission Success in Lebanon (International Journal of Economics and Management Research, 2026)
This study analyzes the influence of internal factors on the success of the Garuda Contingent assignment of the United Nations Interim Force in Lebanon (UNIFIL). The internal factors examined are peronael readiness (X1), covering individual competence, physical and mental readiness, and socio-cultural adaptability, and material readiness (X2), including adequacy of combat equipment, logistical support, and supporting technology. Assignment (Y) measured through mandate achievement, incident reponse speed, stakeholder satisfaction. Using quantitative, explanatory research design, data were collected through questionnaires to 291 respondents from the Garuda Contingent UNIFIL personnel. Data analysis was carried out using SmartPLS software. The results of the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis showed that both personnel readiness (X1) and material readiness (X2) had a positive and significant influence on the success of the assignment (Y). Specifically, the path coefficient from X1 to Y is 0.595 (p < 0.001), and the path coefficient from X2 to Y is 0.305 (p < 0.001), indicating that personnel readiness has a stronger influence on assignment success compared to material readiness. The R-Square value for variable Y is 0.715, indicating that 71.5% of the variation in assignment success can be explained by personnel and material readiness. The implication of this finding is the need for the formulation of policies and strategies that focus on improving personnel readiness, material modernization, and diversifying the role of the contingent to optimize Indonesia's contribution to the peacekeeping mission in Lebanon and in the future.